The Influence Of Leadership And Work Culture On Employee Performance At PT. Semen Tonasa Pangkep Regency - Gilbert Bintang Pratama; Ch. Jeane Tandirerung; Kordiana Sambara (LPPM Universitas Buddhi Dharma, 2025)
Employee performance is one of the main indicators of a company's success. At PT. Semen Tonasa, which is a leading company in cement production in Indonesia, employee performance is greatly influenced by two main factors: leadership and work culture. The work culture at PT. Semen Tonasa includes elements of collaboration, but there are also challenges in terms of effective communication between teams. The impact of a culture that supports collaboration can enhance innovation, but communication barriers can lead to misunderstandings and conflicts within the team. There are fluctuations in employee performance, where some periods show significant performance improvement, while in other periods performance declines. Factors such as changes in leadership or working conditions can contribute to performance fluctuations. Leadership has a significant impact on employee performance at PT. Semen Tonasa. Work culture has a significant impact on employee performance at PT. Semen Tonasa. The research method used is quantitative research and employs multiple linear regression analysis, determinant analysis, and t-test. The research results show that the variables of leadership and work culture simultaneously affect the variable of employee performance. Leadership and work culture significantly affect employee performance. This can be proven through field research, which shows that, on average, all research variables receive positive responses.